Abdominal Cocoon With Intestinal Perforation: A Case Report - Hu, Qiang; Shi, Jianfeng; Sun, Yuanshui (Frontiers in Surgery, 2021)
Introduction: Abdominal cocoon is a very rare abdominal disease. Abdominal cocoon mainly leads to intestinal obstruction, and abdominal cocoon with gastrointestinal perforation is rare. Case presentation: We report a 63 year old man who was admitted to our hospital with "persistent lower abdominal pain for one day". Abdominal CT examination revealed a small amount of free gas in the abdominal cavity, ascites and gastrointestinal perforation.Emergency operation was performed. During the operation, the end of the right lower abdominal ileum was found to be conglutinated and twisted into a mass,local intestinal dilatation and obstruction,local intestinal wall was black and gangrene, and fecal effusion flowed out.The adhesions were carefully separated and the necrotic small intestine was removed. The operation process went smoothly and the patient recovered well after the operation. Conclusion: The cases of intestinal perforation caused by abdominal cocoon are very rare. In clinical work, when we encounter patients with gastrointestinal perforation, we need to carefully ask the history. When the patients have no digestive system diseases in the past, we need to consider the possibility of abdominal cocoon with perforation.